Fully distributed consensus for fuzzy multiagent systems with jointly connected topology. Issue 3 (5th July 2022) - Li, Qinsheng; Yu, Jiafeng; Xing, Wen; Shi, Yan
Abstract: This paper investigates the problem of fully distributed consensus for polynomial fuzzy multiagent systems (MASs) under jointly connected topologies. First, a polynomial fuzzy modeling method is presented to characterize the error dynamics that is constructed by one leader and multiple followers. Then, using the relative state information and the agents' dynamics, a distributed adaptive protocol is designed to guarantee that MASs under jointly connected topologies can achieve consensus in a fully distributed fashion. Utilizing the Lyapunov technique, a relaxed sufficient criterion is proposed to ensure consensus for fuzzy MASs under jointly connected topologies. Moreover, the adaptive coupling weights between neighboring agents can converge to certain values. The derived condition is transformed into a sum‐of‐squares form, which can be solved numerically. We provide an example to illustrate the proposed distributed adaptive consensus technique's validity.